Breaking Bad: a case of Lactobacillus bacteremia and liver abscess - Abdillahi M. Omar; Nastaran Ahmadi; Mutaz Ombada; Joseph Fuscaldo; Nazia Siddiqui; Myra Safo; Swaroopa Nalamalapu (Journal of Community Hospital Internal Medicine Perspectives, 2019)
We present a case of a 46-year-old Hispanic male with a past medical history significant for uncontrolled diabetes presenting with abdominal pain, nausea and vomiting and found to have Lactobacillus bacteremia and liver abscess. A PubMed and Clinical Key literature review of the other known cases of Lactobacillus liver abscess was performed. Through examination of previous case reports, the patient presented in this paper, and the associated risk factors of Lactobacillus liver abscess it is likely that the incidence of this rare condition will increase and would therefore be prudent to further study Lactobacillus as a pathogenic bacteria so that its complications may be better treated and prevented.